The Effect Of Stocking Density and Feeding Rate On Growth and Survival Rate Of Ingir-ingir Larvae (Mystus nigriceps) with Resirculation System - Wiwin Suratman Situmeang; Netti Aryani; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe aim of this research was to determine the effect of stocking density and feeding rate on growth and survival rate of ingir-ingir larvae. This research was conducted from September-Oktober 2018 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The Method used was a Factorial Completely RandomizedDesign with two factors, the first was stocking density with three levels namely 5 larvae/L (S5), 10 larvae/L (S10) and 20 larvae/L (S20). While the second factor wasfeeding rate 40% (F40), 60% (F60) and 80% (F80) of biomass.To minimize errors, each level of treatment was repeated 3 times. The result showed that stocking density and feeding rate were significant on absolute weight, absolute length, average growth rate, survival rate and feed efficiency. The treatment S5F80 (5 larvae/L and feeding rate 80% of biomass weight) were significant(P<0,05) with an absolute weight of 0,67 g, absolute length 3,65 cm, average growth rate of 16,28 %/day, feed eficiency 14,59 % and survival rate 91,33 %. The water quality parameters during research was in optimal range temperature 26,4-27,5°C, pH 5-6and dissolved oxygen 3,6-4,51 mg/l. Keywords : Stocking denstity, Feeding Rate, Growth and Survival rate